Babesiosis in Pregnancy: An Imitator of HELLP Syndrome - Raminder Kaur Khangura; Nayo Williams; Shontreal Cooper; Anne- Marie Prabulos (Thieme Medical Publishers, Inc., 2019)
HELLP syndrome (hemolysis, elevated liver enzymes, and low platelets) is a serious pregnancy complication that can cause significant maternal and neonatal morbidity and mortality. There are several conditions that may occur in pregnancy that may imitate the laboratory findings and clinical presentation of HELLP syndrome. Babesiosis is a parasitic imitator of HELLP syndrome that can be spread by the tick, transfusions, or congenitally. Recognition and treatment of this condition is important to optimize maternal and fetal outcomes.